Targeted solid phase fermentation of the soil dwelling fungus Gymnascella dankaliensis yields new brominated tyrosine-derived alkaloids. Issue 85 (30th August 2016) - Wang, Hao; Dai, Haofu; Heering, Christian; Janiak, Christoph; Lin, Wenhan; Orfali, Raha S.; Müller, Werner E. G.; Liu, Zhen; Proksch, Peter
Abstract : Seven new brominated alkaloids, gymnastatins T–Y (1–6 ) and dankastatin D (7 ), together with three known analogues were isolated from the soil fungus Gymnascella dankaliensis through fermentation on solid rice mediumcontaining NaBr. Abstract : Seven new brominated tyrosine-derived alkaloids, gymnastatins T–Y (1–6 ) and dankastatin D (7 ), together with three known likewise brominated analogues gymnastatins I–K (8–10 ) were isolated from the soil fungus Gymnascella dankaliensis through fermentation on solid rice medium following addition of NaBr. None of these compounds were detected when the fungus was cultured on rice that either lacked NaBr or that contained NaCl instead, indicating a remarkable plasticity of the fungal secondary metabolism. All structures were elucidated on the basis of one and two dimensional NMR spectroscopic analyses and MS data. The absolute configuration of the new gymnastatin T (1 ) was determined by X-ray crystallographic data. All isolated alkaloids showed potent to moderate cytotoxicity against the L5178Y mouse lymphoma cell line with IC50 values ranging from 0.078 to 14.1 μM.